2012
DOI: 10.1016/j.arr.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction in rats and mice: A meta-analysis and review of the evidence for genotype-dependent effects on lifespan

Abstract: Laboratory survival experiments have shown that dietary restriction (DR) can increase median and maximum lifespan. This paper provides a meta-analysis of laboratory experiments that have evaluated the effects of DR on lifespan in rats and mice (1934 – present). In rats, DR increased median lifespan by 14 – 45% in half of all experiments, but in mice the effects of DR have been much weaker (4 – 27%). The least favorable effects of DR on lifespan have been observed among inbred rather than non-inbred mouse strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 122 publications
7
181
2
3
Order By: Relevance
“…All procedures were reviewed and approved by University of Aberdeen ethical approval committee and carried out under a Home Office issued licence compliant with the Animals (Scientific Procedures) Act 1986. This strain is already known to live longer under CR (Turturro et al ., 1999; Swindell, 2012). More information on procedures and measures can be found in Data S10 and the first paper of this series (Mitchell et al ., 2015c).…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were reviewed and approved by University of Aberdeen ethical approval committee and carried out under a Home Office issued licence compliant with the Animals (Scientific Procedures) Act 1986. This strain is already known to live longer under CR (Turturro et al ., 1999; Swindell, 2012). More information on procedures and measures can be found in Data S10 and the first paper of this series (Mitchell et al ., 2015c).…”
Section: Methodsmentioning
confidence: 99%
“…Even though DR repeatedly induced lifespan prolongation in rodents, DR does not increase lifespan in all mouse strains [58]. In wild mice, DR even increased mortality in early life [59].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant lifespan effects in some studies may be due to small sample sizes, whereby single individuals have a large effect on the overall group survival (13,57) . Indeed, and as reviewed in detail elsewhere (8) , contemporary analysis of some of the early rat DR studies suggest that the lifespan extension effects reported may have been somewhat overestimated. Large sample sizes may also produce negligible but significant lifespan effects that might have little relevance to the actual biology (8) .…”
Section: The Universality Of Dietary Restriction On Lifespan and Healmentioning
confidence: 99%
“…Indeed, and as reviewed in detail elsewhere (8) , contemporary analysis of some of the early rat DR studies suggest that the lifespan extension effects reported may have been somewhat overestimated. Large sample sizes may also produce negligible but significant lifespan effects that might have little relevance to the actual biology (8) . There are also some suggestions that DR may affect the ageing trajectory differently in mice and rats, and this may also be the case within different strains.…”
Section: The Universality Of Dietary Restriction On Lifespan and Healmentioning
confidence: 99%